A comparison of Scopus and WoS database subject classifiers in mathematical disciplines - Efremenkova, V. M.; Gonnova, S. M. (Scientific and technical information processing, 2016)
This paper presents a method for comparing the subject headings of Scopus and WoS classifiers that has been tested based on examples in the field of mathematical disciplines. Semantic relationships of subject headings are explored by using intelligent analysis of keyword and expression clustering. The results are presented in the form of a correspondence table for the subject headings of the classifiers.